Health education to support survivors of LGBTQA+ conversion practices: A participatory approach to professional training - Timothy W. Jones; Jennifer Power; Tiffany M. Jones; Joel R. Anderson; Nathan Despott; Maria Pallotta-Chiarolli (Health Education Journal, 2026)
Background: Conversion practices – efforts to change or suppress a person’s sexual orientation or gender identity – cause profound and enduring harm. Survivors frequently report difficulty accessing safe, informed, and affirming mental health care, highlighting critical gaps in health workforce education and training. Aim: In this paper, we describe our research team’s journey when undertaking a participatory action research project to investigate survivors’ recovery needs and practitioners’ information needs. Approach: Guided by an intersectional, trauma-informed framework, the project privileged lived experience alongside practitioner and researcher expertise, and actively challenged dominant narratives that centre white, US, Christian contexts while overlooking informal and culturally embedded forms of conversion practices. These insights informed the co-production of an accredited health professional education programme, developed collaboratively with survivor advocates, researchers, and training designers. The programme was delivered nationally and internationally, co-facilitated by people with lived experience, and designed to support reflective learning and applied practice across diverse cultural, faith, and community contexts. Outcomes: Among exit-survey respondents, 96% of participants agreed or strongly agreed that the training improved their knowledge of conversion practices and their capacity to support survivors in ethical, affirming, and trauma-informed ways. Beyond knowledge transfer, the process fostered institutional and cultural change, informing subsequent education-focused initiatives with religious leaders to improve safety in pastoral care. Conclusions: This article reflects on the methodological and ethical considerations of translating participatory research into health education practice, the importance of survivor leadership, and the importance of co-produced approaches to advancing equity, inclusion, and systemic change.